Russian experience and perspectives of quality assurance in healthcare through standards of care. Issue 3 (September 2016) - Vlassov, Vasiliy V.
Abstract: Objectives: The main reform of healthcare system in Russia had begun by introduction of compulsory healthcare insurance in 1993. Since this time, Russia went through number of steps of healthcare system modernization. Most attention was paid to the resource allocation, medical equipment and drug provision, the problem of the low quality of care was repeatedly addressed. Major direction of the efforts was the creation of obligatory technical standards of care. Methods: I studied the volume of publication found in MEDLINE for period 1991–2014 and in the relevant Russian journals not covered by MEDLINE as well as legislation on health care introduced since 1991. Results: The review found that despite some increase in volume of funding of health care system, and provision of incentives for quality, the progress with health care quality assurance is slow. The methodology of development of evidence based guidelines is not accepted. The control over conflict of interest of participants of the development of the guiding documents is not introduced. Economic factors are not systematically addressed in decisions on provision of health care interventions. The practice of the health technology assessment does not exist. The system of financial incentives for the quality of care dominates and is developing without evidence based criteria and evidence of its efficacy. Conclusion: The documents prescribing quality healthcare are developing non-systematically in Russia. The acceptance of the modern methodology of guideline development, health technology assessment and control over conflict of interest is needed as a minimum prerequisite for the progress in the quality assurance. Highlights: Russian health care system reform did not solve the problem of unlimited promise and limited funding. Development of the standards of care prescribing the volume and cost of care failed. Russian health system is returning to the tried in 1990-s development of evidence based guidelines.